FluxProg 2.0 - Extended Version of a Visual Tool for Teaching Programming Logic Using Flowcharts with Real and Simulated Robots - Gutierrez, Matheus Biscaya; Fabro, Joao Alberto; Cordeiro, Andre Cristiano (Proceedings (Brazilian Robotics Symposium. Online), 2024)
This paper presents a new teaching tool with the goal of facilitating the learning of basic programming concepts among high school students and university freshmen. The tool incorporates a user-friendly visual interface and robotics, expanding on the existing Fluxprog project. New features were implemented, such as variables, logical and mathematical operations, conditional structures, and loops, to motivate students to engage in challenges that promote logical thinking. This paper presents the design, implementation and evaluation of a programming teaching tool using a visual language based on flowcharts, with subsequent data collection through a questionnaire and analysis of preliminary results to evaluate the user's experience while interacting with the tool.